Interregional Connectivity among Indian Immigrants: A Series of Protests against Exclusion from Canada, the US Mainland and Manila in the Early 20th Century - Kaori Mizukami (International Quarterly for Asian Studies, 2023)
This paper examines a series of refusals to admit Indian immigrants into North America in the early twentieth century and the resulting protest movements in Canada, the US mainland and the Philippines. By examining these events, the study aims to enhance our comprehension of Indian immigrants’ agency in shaping their interregional mobility and connectivity. Indians repeatedly faced de facto exclusion from these places, but they devised strategies to facilitate migration, and in response, Canadian and US authorities tightened control, leading to further resistance. Throughout these cycles of restriction and resistance, Indian migrants combined the knowledge and experiences acquired in Manila and North America, countering immigration policies and strengthening interregional connectivity. Understanding the interregional connectivity among Indian immigrants is key to understanding why Indians from different regions were actively involved in the anti-British Ghadar movement and the Komagata Maru incident. This paper focuses on the agency of Indians in Manila and examines the reasons behind their engagement in these events.